2007
DOI: 10.1300/j106v14n02_01
|View full text |Cite
|
Sign up to set email alerts
|

Porch Reads

Abstract: Leisure reading in America has declined in the last 20 years, especially among 18 to 24 year olds. Studies show, however, that a positive relationship exists between college students' academic achievement and the time they spend in recreational reading. Reading for pleasure improves reading comprehension, writing style, vocabulary, spelling, and grammatical development. Librarians at the Roesch Library, University of Dayton (OH), collaborated with colleagues in Residence Education on a yearlong pilot recreatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…The exposure to a diverse array of literary genres reinforces students' reading competencies and fosters their aesthetic sensibilities, particularly concerning literary discourse, while also fostering the development of social and analytical skills in literature and written communication in general (Martin-Chang et al, 2021;Smith & Galbraith, 2011). Simultaneously, students develop the skills to distinguish intellectual and artistic works that accurately represent the beliefs and cultural influences of their time periods, thus enhancing their historical consciousness and providing experiential insight into the sociopolitical and aesthetic dimensions of cultural history (Gauder et al, 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…The exposure to a diverse array of literary genres reinforces students' reading competencies and fosters their aesthetic sensibilities, particularly concerning literary discourse, while also fostering the development of social and analytical skills in literature and written communication in general (Martin-Chang et al, 2021;Smith & Galbraith, 2011). Simultaneously, students develop the skills to distinguish intellectual and artistic works that accurately represent the beliefs and cultural influences of their time periods, thus enhancing their historical consciousness and providing experiential insight into the sociopolitical and aesthetic dimensions of cultural history (Gauder et al, 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…A su vez, también se identifican investigaciones en las que se citan otros estudios que han demostrado cómo la lectura recreativa contribuye a que las personas tengan mayores habilidades comunicativas, de comprensión de textos y adquisición de vocabulario (Rathe y Blankenship, 2006;Gauder et al, 2007). También se evidencia que fomenta el pensamiento crítico (Dewan, 2013;Brookbank et al, 2018), creativo, imaginativo y lúdico (Ramírez, 2015), y el apoyo a la adquisición de una segunda lengua (Bordonaro, 2011).…”
Section: Beneficios Y Evaluación De Los Programasunclassified
“…Despite the heartening proliferation of promotional reading programs in academic libraries, many studies reported only their limited success and sustainability ( Gauder et al, 2007 ; Bosman et al, 2008 ; Fajardo, 2010 ; Chesnut, 2011 ; Mackay and Tarulli, 2015 ; Dali and McNiff, 2020 ). We view the lack of a differentiated approach to promote reading and the low level of reader engagement in activities as one of the reasons for the limited success and short lifespan of reading initiatives.…”
Section: Introductionmentioning
confidence: 99%